Climate Variability Impacts and Coping Strategies in Malipati Communal Area, Chiredzi District, Southeast Zimbabwe. (5th September 2022) - Dhliwayo, Itai; Mutanga, Chiedza Ngonidzashe; Mashapa, Clayton; Muboko, Never; Gandiwa, Edson
Abstract : The spatial-temporal impacts and coping strategies to climate variability vary across human communities. Focusing on Malipati Communal Area in Chiredzi District, southeast Zimbabwe, the study analysed the impacts of climate variability and coping strategies adopted by local communities. Data were collected between May and June 2018 in five (5) villages in Ward 15 of Malipati Communal Area, where a total of 133 participants were involved through focus group discussions, questionnaires, and key informant interviews. The results showed an increase in livestock mortality and in contrast no significant changes in crop yields between 1990 and 2018. Further, the study established that local communities have negative perceptions towards the adaptive coping strategies to climate change, especially on the production of small grains. There is a need for other innovative strategies to enable communities to continuously buffer the impacts of climate variability inclusive of diversifying economic activities.